2013
DOI: 10.1037/a0032291
|View full text |Cite
|
Sign up to set email alerts
|

The effects of achievement goals on emotions and performance in a competitive agility task.

Abstract: The link between achievement goals and emotions has received much attention in the sport psychology literature. However, experimental studies are lacking. In this experiment, we investigated the effects of achievement goals on (a) emotions experienced before and after a competitive agility task and (b) perceived and actual agility performance. Male (n = 60) and female (n = 60) undergraduate students were assigned to a task, ego, or control group and following a practice session, they competed in a speed agilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Specifically, in this study, we assessed actual performance, whereas previous research assessed "perceived" performance. Indeed, other studies have also shown discrepancy in the findings pertaining to perceived and actual performance (e.g., Dewar et al, 2013); thus results involving perceived performance may not fully generalize to actual performance.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Specifically, in this study, we assessed actual performance, whereas previous research assessed "perceived" performance. Indeed, other studies have also shown discrepancy in the findings pertaining to perceived and actual performance (e.g., Dewar et al, 2013); thus results involving perceived performance may not fully generalize to actual performance.…”
Section: Discussionmentioning
confidence: 86%
“…The stem "During the task, I felt..." was followed by items measuring happiness (e.g., "joyful", "cheerful"), anxiety (e.g., "anxious", "nervous"), and anger (e.g., "annoyed", "furious"). Previous studies have supported the construct validity and internal consistency of the three subscales when used after competition (e.g., Dewar, Kavussanu, & Ring, 2013).…”
Section: Methodsmentioning
confidence: 85%
“…The study utilized an experimental design that sought to induce a particular achievement goal state through the use of a detailed manipulation script. Many researchers have used a similar design to manipulate achievement goal states in a variety of tasks including dart throwing, golf putting, an agility drill, and basketball dribbling (Elliot et al, 2006;Kavussanu, Morris, & Ring, 2009;Ntoumanis et al, 2009;Dewar, Kavussanu, & Ring, 2013). These studies have typically included a manipulation check in the design as a way to test whether the participants adopted the desired goal or not.…”
Section: Main Analysesmentioning
confidence: 99%
“…These studies have typically included a manipulation check in the design as a way to test whether the participants adopted the desired goal or not. A common practice among researchers, when dealing with manipulations, is to remove the participants who are found to be incongruent with the manipulation (Dewar et al, 2013).…”
Section: Main Analysesmentioning
confidence: 99%
See 1 more Smart Citation